THE EFFECT OF ORGANIZATIONAL CLIMATE, WORK ENVIRONMENT AND COMPENSATION ON EMPLOYEE WORK SPIRIT AT BANK BNI FATMAWATI BRANCH OFFICE - Saputra, Endra; Taufiq, Kemal; Hanaffy, Jamal (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to determine and analyze the magnitude of the influence of organizational climate on employee work enthusiasm at Bank BNI Fatmawati branch office, To determine and analyze the magnitude of the influence of the work environment, the influence of compensation on employee work enthusiasm, the influence of organizational climate, work environment and compensation on employee work enthusiasm at Bank BNI Fatmawati branch office. This study uses a quantitative approach using descriptive and associative research types. The population studied was 200 Bank BNI Fatmawati branch office employees. The sampling technique in this study was the total sampling technique. The analysis technique used in this study was the SPSS version 20 program, by processing classical assumption test data including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, followed by hypothesis testing using multiple regression analysis and partial tests (t-test). The results showed that there was an influence of Organizational Climate on Employee Work Spirit at Bank BNI Fatmawati branch office, as evidenced by the tcount value> ttable (3.066> 1.971). There is no influence of organizational environment on Employee Work Spirit at Bank BNI Fatmawati branch office, proven by the calculated t value > t table (0.002 < 1.971). with a significant level of 0.000 < 0.05, while the Adjusted R Square value of 0.209 or 20.9% of the variables Organizational Climate (X1), Organizational Climate (X2) and Compensation (X3) simultaneously (together) influence the variable Employee Work Spirit (Y) and the remaining 79.1% is influenced by other factors not examined in this study.